Analisis Kalimat Bervariasi Berita-Perintah-Tanya Dan Hubungan Makna Antar Kalimat Pada Teks Terjemahan Alquran Surat Albaqarah - DWI UTAMI, WINDA; , Prof.Dr.Markhamah,M.Hum (2016)
The various sentences of news-imperative-interrogative have close relation of meaning to each other. This research has two aims 1) Explaining the various sentences of news-imperative-interrogative in the translation texts of Alquran of Albaqarah epistle. 2) Explaining the relationship between the meanings of the various sentences in the translation texts of Alquran of Albaqarah epistle. This is a kind of research of qualitative research and data collection is using observation method (metode simak), with a basic technique is tapping technique, and continuance of this technique of this observation method applied in this research is writing technique. Validity of data technique is using triangulation techniques are source triangulation and theory triangulation while the data analysis technique is using Comparing Technique (Teknik Padan). The results of this research showed that every paragraph in the epistle which serve as examples of this research there are varied sentences of news-imperative-interrogative that is in paragraph 13, paragraph 30, paragraph 33, paragraph 243, paragraph 246, paragraph 259, and paragraph 260. Varied sentences of imperative-news can be found in paragraph 25, paragraph 31, paragraph 36, paragraph 38 and paragraph 264. Varied sentences of news-interrogative can be found in paragraph 26, paragraph 247, and paragraph 258. The relationship of the meaning in the translation texts of Alquran of Albaqarah epistle was generally each of the sentences analyzed there is the relationship possess imperative, announcement, and assertion that strengthens and interconnected meanings to each other sentences.